Exposure to Decreased pH and Caffeine Affects Hemocyte Parameters in the Mussel Mytilus galloprovincialis - Marco Munari; Valerio Matozzo; Giuditta Benetello; Verena Riedl; Paolo Pastore; Denis Badocco; Maria Gabriella Marin (Journal of Marine Science and Engineering, 2020)
Combined effects of reduced pH, as predicted under climate change scenarios, and the most popular and widely used stimulant caffeine were assessed in hemocyte parameters of the mussel Mytilus galloprovincialis, being hemocytes involved in immune defense. Bivalves were exposed for one week to natural pH (8.1) and two reduced pH values (pH −0.4 units and pH −0.7 units). Exposure continued for additional two weeks, both in the absence and in the presence of environmentally relevant concentrations of caffeine (0.05 and 0.5 µg/L). Hemocyte parameters (total hemocyte count, hemocyte volume and diameter, neutral red uptake and hemocyte proliferation) were measured after 7 days of exposure to pH only, and after 14 (T1) and 21 (T2) days of exposure to the various pH*caffeine combinations. At all sampling times, pH significantly affected all the biological variables considered, whereas caffeine exhibited a significant influence at T2 only. Among the various hemocyte parameters, caffeine caused a significant increase in total hemocyte count at T2, and in hemocyte volume and diameter at both T1 and T2, when a significant interaction between pH and caffeine was also found. Overall, results demonstrated that hemocyte functionality was strongly influenced by the experimental conditions tested. Further studies are needed to assess combined effects of climate changes and emerging contaminants on bivalve immune system when challenged with environmental pathogens.